The substructure of extremely hot summers in the Northern Hemisphere - Röthlisberger, Matthias; id_orcid:0 000-0003-0904-9495; Sprenger, Michael; Flaounas, Emmanouil; Beyerle, Urs; id_orcid:0 000-0002-6464-0838; Wernli, Heini; id_orcid:0 000-0001-9674-4837 (Copernicus, 2020)
In the last decades, extremely hot summers (here- after extreme summers) have challenged societies worldwide through their adverse ecological, economic and public-health effects. In this study, extreme summers are identified at all grid points in the Northern Hemisphere in the upper tail of the June–July–August (JJA) seasonal mean 2 m temperature (T2m) distribution, separately in ERA-Interim (ERAI) re- analyses and in 700 simulated years with the Community Earth System Model (CESM) large ensemble for present-day climate conditions. A novel approach is introduced to characterise the substructure of extreme summers, i.e. to elucidate whether an extreme summer is mainly the result of the warmest days being anomalously hot, of the coldest days being anomalously mild or of a general shift towards warmer temperatures on all days of the season. Such a statistical characterisation can be obtained from considering so-called rank day anomalies for each extreme summer – that is, by sorting the 92 daily mean T2m values of an extreme summer and by calculating, for every rank, the deviation from the climatological mean rank value of T2m. Applying this method in the entire Northern Hemisphere reveals spatially strongly varying extreme-summer substructures, which agree remarkably well in the re-analysis and climate model data sets. For example, in eastern India the hottest 30 d of an extreme summer contribute more than 65 % to the total extreme-summer T2m anomaly, while the colder days are close to climatology. In the high Arctic, however, extreme summers occur when the coldest 30 d are substantially warmer than they are climatologically. Furthermore, in roughly half of the Northern Hemisphere land area, the coldest third of summer days contributes more to extreme summers than the hottest third, which highlights that milder-than-normal coldest summer days are a key ingredient of many extreme summers. In certain regions, e.g. over western Europe and western Russia, the substructure of different extreme summers shows large ...